Integrasi Kebijakan Pemerintah dalam Pengembangan Pariwisata Kota Tanjungpinang dan Kabupaten Bintan - Erika Florida Damiani Ngasi; Eki Darmawan (Dinasti Review, 2024)
Tanjungpinang City and Bintan Regency are regions in the Riau Islands which are also popular tourist destinations due to their abundant natural resources. However, there are several policy constraints in promoting these two tourist destinations in each respective region. Tourism development needs to consider the economy of a region to meet good Regional Revenue Budget. Therefore, policy integration becomes a solution to the overlapping policies between the two regions in achieving the common goals of promoting and marketing Creative Economy in the Riau Islands. The aim of this study is to analyze the extent to which the integration of regional government policies in the development of tourism in Tanjungpinang City and Bintan Regency has been achieved. This article uses a qualitative research approach where data findings from observations or primary data as well as secondary data such as interviews and scientific journal articles are interpreted from the researcher's perspective. The lack of connectivity between the two regions is attributed to the failure to achieve the goals of the medium-term regional development plan and the lack of connectivity between the regions in both infrastructure and marketing their tourism packages. The hope is to achieve synchronization between the tourism policies taken by the Tanjungpinang City and Bintan Regency Governments and close cooperation between local governments, the private sector, and local communities through collaboration between the Tanjungpinang City and Bintan Regency Governments.